Enhancing Web Search by Promoting Multiple Search Engine Use - White, Ryen W.; Richardson, Matthew; Bilenko, Misha; Heath, Allison (Proceedings of the 31st Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2008), 2008)
We let users keep their default engine and suggest an alternative engine if we estimate it performs better for the current query.